Morphology and ecology of fishery important, cryptic teleosts in Australia - Takahashi, Miwa (Curtin University, 2021)
Cryptic teleosts pose challenges to accurate species identification due to their similar morphologies which hinders biological, ecological and fishery assessments. I validated the use of cost-effective identification tools using otolith and body morphometry for eleven cryptic teleosts. Inter- and intra-specific partitioning of diet and habitat was identified between the juveniles and adults of cryptic red snappers, using DNA metabarcoding dietary analyses with the custom blocking primers and species distribution modelling.